Confidentiality of personal health information used for research. Issue 7560 (20th July 2006) - Kalra, Dipak; Gertz, Renate; Singleton, Peter; Inskip, Hazel M
Abstract : Researchers must balance the quest for better health for all against the need to respect the privacy of research participants. What needs to be done to ensure best practice?